Analisis Penggunaan Lahan Tahun 2013 terhadap Ketersediaan Air di Sub Daerah Aliran Sungai Blongkeng - Sari, Dewi Novita; , Drs. Yuli Priyana, M.Si; , Drs. Munawar Cholil, M.Si (2015)
Farmland drought that hit some areas at Blongkeng Sub Watershed in 2013 affect of the water balance. Potential of water supply at non-domestic landuse is affected by the water needs in each landuse patterns. Decreasing of land for uptake and catchment rainfall is one of the factors that affect water balance system. The purpose of this research 1) Estimated availability of water at Blongkeng Sub Watershed, 2) Knowing the water needs based on the pattern of land use in 2013 at Blongkeng Sub Watershed, and 3) Analyze the water balance by months of wet and dry season preformance scope of Sub Watershed assessment. The research method using Thronthwaite Matter water balance, data sources of hidrometereologi such as rainfall and temperature from 3 stations around Blongkeng Sub Watershed for 10 years (2004-2013). Water needs from pattern of land use obtained through data processing based Remote Sensing and Geographic Information System. Landsat 8 recording June 2013 is processed into maps of land use in 2013 Blongkeng Sub Watershed, conducted a survey with purposive sampling method. Size of each land use can be known from the calculation of water needs. The potential of water availability is a comparison between amount of water available requirements. Results of this research 1) Potential of water availability in each month is the lowest at rice field ranged from 6-180 mm3/year while the highest in each month is open land and lava - volcanic mudflow range between 6000-3900000 mm3/year, 2) The water needs is directly inversely with the water availability, the lowest requirement is open land with average 1000 mm3/year while the highest is a rice land with an average 4.5 to 12 million mm3/year, 3) Percentage value of the deficit / surplus each land use patterns in the wet season has surplus between other forest land, mix plantations, lava - volcanic mudflow, and open land while in the dry season has deficit at the land around settlements, rice field, and terrain/fields. Vulnerability to drought at Blongkeng Sub Watershed predicted occur in August - October. Keywords: Drought, Water Availability, Water Requirements, Thronthwaite Matter, Water Balance